Horizontal and Vertical (Buyer-Supplier) Spillovers from Foreign Direct Investment : Determinants of Malaysian Establishments' Total Factor Productivity - Khalifah, Noor Aini; Mohd Salleh, Salmah; Adam, Radziah (2010)
This study examines the issue of indirect technology transfer through both horizontal and vertical spillovers from foreign direct investment (FDI). Combining both input-output data for 2000 and a balanced micro-panel data set for the period 2000-2004, we estimate total factor productivity (TFP) of establishments as a function of the different extent of foreign presence and inter industry linkages; amongst other explanatory variables.